Implementation of Presidential Regulation Number 39 of 2019 Concerning One Data Indonesia in Langkat District Government - Syahpitri, Eliana; Salmiah, Nina Siti; Batubara, Beby Masitho (Journal of Public Representative and Society Provision, 2025)
One Data Indonesia (Satu Data Indonesia/SDI) is a national policy designed to establish high-quality, integrated government data. Mandated by Presidential Regulation No. 39 of 2019, all government institutions, including local governments, are required to implement SDI to support effective planning, monitoring, and evaluation of regional development. This study analyzes the implementation of SDI in Langkat Regency, identifies key challenges, and proposes strategies for more effective adoption. Employing a descriptive qualitative approach, the study gathers data through observations, interviews, and documentation. Informants include members of the Langkat Regency SDI implementation team, such as representatives from Bappeda, BPS, Diskominfostand, and regional apparatus organizations (RAOs). Findings indicate that SDI implementation in Langkat is still in its early stages. Initial progress includes the establishment of local regulations, the formation of SDI-related institutions, and the development of the Langkat SDI Portal. However, several significant obstacles hinder full implementation. These include suboptimal coordination among RAOs, limited human resources with expertise in statistics and data management, inadequate technological infrastructure, low internet connectivity, lack of system integration, and insufficient understanding and commitment to SDI principles. Moreover, awareness of SDI’s benefits among stakeholders remains low. Despite these challenges, SDI presents a strategic opportunity for enhancing data governance at the regional level. Strengthening institutional coordination, investing in capacity building, improving infrastructure, and increasing awareness are essential to ensure the successful and sustainable implementation of SDI in Langkat Regency.